Cross-cultural adaptation and reliability of the Arabic version of Children's Hand-use Experience Questionnaire (CHEQ). Issue 1 (June 2022) - Amer, Ahmed; Alomari, Mahmoud A.; Jarl, Gustav; Ajarmeh, Majd M; Migdadi, Fathi; Eliasson, Ann-Christin; Hermansson, Liselotte
Background: Validated outcome measures are essential for assessment and treatment of children with disabilities. The Children's Hand-use Experience Questionnaire (CHEQ) was developed and validated for use in Western countries for children with unilateral hand dysfunction. This study aimed to perform a cross-cultural adaptation and investigate reliability for the Arabic CHEQ. Methods: Translation and cross-cultural adaptation were performed in four phases: (i) forward-translation and reconciliation with feedback from parents and typically developing children from Jordan ( n = 14); (ii) backward-translation and review; (iii) cognitive debriefing with parents and/or their children with unilateral hand dysfunction ( n = 17); and (iv) review and proofreading. In the psychometric analyses, 161 children from Jordan (mean age [SD] 10y 8 m [5y 8 m]; 88 males) participated. Internal consistency was evaluated with Cronbach's alpha. Test-retest reliability was evaluated in 39 children with intraclass correlation coefficient (ICC) and weighted kappa (κ). Results: Synonyms of four words were added to accommodate for different Arabic dialects. On average, 93% of children with unilateral hand dysfunction and their parents understood the CHEQ items. One response alternative, ' Get help ', to the opening question was unclear for 70% of the respondents and need further explanation. Two items about using a knife and fork were difficult to comprehend and culturally irrelevant. High internal consistency was demonstrated (Cronbach's alphas 0.94- 0.97) and moderate to excellent ICC (0.77–0.93). For 18 individual items, κ indicated poor to good agreement (κ between 0.28 and 0.66). Conclusions: After the suggested minor adjustments, the Arabic CHEQ will be comprehensible, culturally relevant and reliable for assessing children with unilateral hand dysfunction in Jordan.